Tropoelastin: A Novel Marker for Plaque Progression and Instability. (August 2018) - Phinikaridou, Alkystis; Lacerda, Sara; Lavin, Begoña; Andia, Marcelo E.; Smith, Alberto; Saha, Prakash; Botnar, René M.
Abstract : Background: Elastolysis and ineffective elastogenesis favor the accumulation of tropoelastin, rather than cross-linked elastin, in atherosclerotic plaques. We developed gadolinium-labeled tropoelastin-specific magnetic resonance contrast agents for tropoelastin imaging in animal models. Methods and Results: Two peptides, VVGSPSAQDEASPLS and YPDHVQYTHY, were selected to target tropoelastin. In vitro binding, relaxivity, and biodistribution experiments enabled characterization of the probes and selecting the best candidate for in vivo magnetic resonance imaging. Magnetic resonance imaging was performed in atherosclerotic apolipoprotein E–deficient mice and New Zealand white rabbits with stable and rupture-prone plaques using a gadolinium-labeled tropoelastin-specific magnetic resonance contrast agent. In addition, human carotid endarterectomy specimens were imaged ex vivo. The VVGSPSAQDEASPLS-based probe discriminated between tropoelastin and cross-linked elastin (64%±7% versus 1%±2%; P =0.001), had high in vitro relaxivity in solution (r1-free =11.7±0.6 [mmol/L] −1 s −1, r1-bound to tropoelastin =44±1 [mmol/L] − 1 s − 1 ), and favorable pharmacokinetics. In vivo mice vascular enhancement (4 weeks=0.13±0.007 mm 2, 8 weeks=0.22±0.01 mm 2, 12 weeks=0.33±0.01 mm 2 ; P <0.001) and R1 relaxation rate (4 weeks=[0.90±0.01]/s, 8 weeks=[1.40±0.03]/s, 12 weeks=[1.87±0.04]/s; P <0.001) increased with atherosclerosis progression after gadolinium-labeled tropoelastin-specific magnetic resonance contrast agent injection. Conversely, statin-treated (0.13±0.01 mm 2 ; R1 =[1.37±0.03]/s) and control (0.10±0.005 mm 2 ; R1 =[0.87±0.05]/s) mice showed less enhancement. Rupture-prone rabbit plaques had higher R1 relaxation rate compared with stale plaques (R1 =[2.26±0.1]/s versus R1 =[1.43±0.02]/s; P =0.001) after administration of the gadolinium-labeled tropoelastin-specific magnetic resonance contrast agent that allowed detection of rupture-prone plaques with high sensitivity (84.4%) and specificity (92.3%). Increased vascular R1 relaxation rate was observed in carotid endarterectomy plaques after soaking (R1pre =[1.1±0.26]/s versus R1post =[3.0±0.1]/s; P =0.01). Ex vivo analyses confirmed the magnetic resonance imaging findings and showed uptake of the contrast agent to be specific for tropoelastin. Conclusions: Magnetic resonance imaging of tropoelastin provides a novel biomarker for atherosclerotic plaque progression and instability. Abstract : Supplemental Digital Content is available in the text.